Long-term efficacy of reduced-intensity versus myeloablative conditioning before allogeneic haemopoietic cell transplantation in patients with acute myeloid leukaemia in first complete remission: retrospective follow-up of an open-label, randomised phase 3 trial. Issue 4 (April 2018) - Fasslrinner, Frederick; Schetelig, Johannes; Burchert, Andreas; Kramer, Michael; Trenschel, Rudolf; Hegenbart, Ute; Stadler, Michael; Schäfer-Eckart, Kerstin; Bätzel, Michael; Eich, Hans; Stuschke, Martin; Engenhart-Cabillic, Rita; et al.
Summary: Background: The impact of the intensity of conditioning before allogeneic haemopoietic cell transplantation (HCT) has been studied in a randomised phase 3 trial comparing reduced-intensity conditioning with myeloablative conditioning in patients with acute myeloid leukaemia in first complete remission. Because of the short follow-up of the original trial, whether reduced-intensity conditioning increases the risk of late relapse compared with myeloablative conditioning remained unclear. To address this question, we present retrospective 10-year follow-up data of this trial and focus on late relapse. Methods: The original randomised phase 3 trial included patients aged 18–60 years, with intermediate-risk or high-risk acute myeloid leukaemia, an adequate organ function, and an available HLA-matched sibling donor or an unrelated donor with at least nine out of ten HLA alleles matched. Patients were randomly assigned (1:1) to 120 mg/m 2 fludarabine combined with four 2 Gy doses of total-body irradiation (reduced-intensity conditioning) or six 2 Gy doses of total-body irradiation and 120 mg/kg cyclophosphamide (myeloablative conditioning). The primary and secondary efficacy endpoints of this trial have been published previously. In this retrospective, long-term follow-up analysis, data were collected from medical reports from individual participating study centres, and from physician and patient interviews. Endpoints included in this analysis were cumulative relapse incidence, overall survival, disease-free survival, and non-relapse mortality in the original study population and in patients alive and relapse-free at 12 months after HCT (landmark analysis). 10-year time to event rates were calculated in the intention-to-treat population and were compared with the Gray test. The trial is registered withClinicalTrials.gov, numberNCT00150878 . Findings: In the original trial, 195 patients were randomly assigned to receive reduced-intensity conditioning (n=99) or myeloablative conditioning (n=96). For this retrospective analysis, data were collected with a nearly complete follow-up (completeness index 99%). Median follow-up time for surviving patients was 9·9 years (IQR 8·5–11·4), during which the cumulative incidence of relapse in the complete study population was identical in both groups (30% [95% CI 20–39] in the reduced-intensity conditioning group vs 30% [21–40] in the myeloablative conditioning group; Gray test p=0·99). Relapse occurred at a median of 5·0 months (IQR 3·0–8·8) in the reduced-intensity conditioning group versus 9·5 months (4·5–20·5) in the myeloablative conditioning group. 10-year disease-free survival was 55% (95% CI 45–66) in the reduced-intensity conditioning group and 43% (34–55) in the myeloablative conditioning group (hazard ratio [HR] 0·76 [0·51–1·14]; p=0·19). 10-year non-relapse mortality was 16% (95% CI 8–24) in the reduced-intensity conditioning group and 26% (17–36) in the myeloablative conditioning group (subdistribution HR 0·60 [95% CI 0·32–1·11]; Gray test p=0·10). The incidence of long-term toxicities associated with total-body irradiation was comparable; secondary malignancies occurred in six (6%) of 94 patients in the reduced-intensity conditioning group and five (6%) of 90 in the myeloablative conditioning group (p=1·00). Interpretation: There is no evidence that reduced-intensity conditioning increases the risk of late relapse compared with myeloablative conditioning. Given that the reduced-intensity conditioning group in the original trial was associated with lower early morbidity and toxicity, reduced-intensity conditioning with moderately reduced total-body irradiation doses could be the preferred conditioning strategy for patients with acute myeloid leukaemia who are younger than 60 years and transplanted in first complete remission. Funding: None.